Kinerja Balai Badan Pengawas Obat dan Makanan Terhadap Peredaran Kosmetik Berbahaya di Kota Makassar - Hilyatul Jannah; Fatmawati A Mappasere; Nuryanti Mustari (Jurnal Administrasi Publik, 2024)
The goal of this study is to determine how Balai Besar POM Makassar performs in terms of unsafe cosmetics distribution. This research employs a descriptive qualitative approach. Data were collected through observation and interviews. The study's findings indicate that BPOM's effectiveness in supervising the circulation of harmful cosmetics in Makassar is satisfactory but might be improved. Despite BPOM's efforts to control illegal cosmetics and reach out to the public, numerous unsafe cosmetic items continue to circulate in the market. As a result, more serious and integrated efforts are required by BPOM, cosmetics manufacturers, and the general public to ensure that cosmetics on the market are safe and do not jeopardize consumer health. This can be seen from the indicators used, namely:1) work quality, 2) work quantity, 3) timeliness, 4) performance effectiveness, 5) work independence. BPOM Makassar City's performance is said to be optimal if it meets all of these indicators.